THE COGNITIVE PROCESS OF WRITING DESCRIPTIVE TEXT BY THE TENTH GRADE STUDENT OF MADRASAH ALIYAH SWASTA NURUL HAKIM MEDAN - Amelia, Fitri (Faculty of Tarbiyah nad Teacher Training, 2021)
This research was aimed describing how the student’s cognitive process of writing descriptive text. The method in this research used descriptive qualitative research method which analyzed the data in the word form. The researcher conducted in the tenth grade student of Madrasah Aliyah Swasta Nurul Hakim which consist of a student as informant, three students as supporting informant and a teacher as supporting informant. The data of this research obtained from observation and protocol interview. This research collected some important information from the student about the cognitive process in writing. The results of the data analysis showed that the student cognitive process in writing descriptive text occurs in the five stages, such as; selecting the title, organizing the ideas, developing the ideas, translating the text and reviewing the text.Keywords: The Cognitive Process, writing, Descriptive Text